(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Rising environmental standards for treated waste water necessitates to improve current waste water treatment methods or to look for the new ones. Often this task is rather difficult because new or modified methods have to be investigated thoroughly and the main parameters for process modeling and effectiveness estimation have to be set. Biomass concentration in biosorption process is important technological parameter though there is no accurate technique for its estimation. Thermal dissociation technique to determine biomass concentration was developed as an alternative to the standard volatile suspended solids (VSS) method. Biomass content is important for the technological calculations of the system, estimation of the oxidation potential and for the evaluation of biomass growth in accordance to decomposed pollutants, etc. Thermal dissociation technique is based on the difference in the sorbent and biomass burn out temperatures. The biomass content research results are given for sand, gravel and for activated carbon BAS-A.